Study of the alleviation effects of a combination of Lactobacillus rhamnosus and inulin on mice with colitis. Issue 5 (24th April 2020) - Liu, Zhijing; Liu, Fei; Wang, Wan; Sun, Changbao; Gao, Da; Ma, Jiage; Hussain, Muhammad Altaf; Xu, Cong; Jiang, Zhanmei; Hou, Juncai
Abstract : Ulcerative colitis (UC) is a common inflammatory bowel disease (IBD) that has serious harmful effects on human health. Abstract : Ulcerative colitis (UC) is a common inflammatory bowel disease (IBD) that has serious harmful effects on human health. Lactobacillus rhamnosus, a probiotic, has a strong colonization and adhesion effect and improves the intestinal health of the host. Inulin has good anti-inflammatory effects and can promote the proliferation of beneficial intestinal bacteria. The purpose of this study was to investigate the alleviating effects of L. rhamnosus 1.0320 in combination with inulin on UC, examining the resulting changes in intestinal flora. A UC model was established by having mice freely drink a 3% (w/v) dextran sodium sulphate (DSS) solution for seven days. After successful modeling, the mice were given antibiotics, L. rhamnosus 1.0320 by itself, inulin by itself, and L. rhamnosus 1.0320 combined with inulin as an intragastric intervention for 28 days. The abundance and structural changes of bacteria in the intestinal content of mice were analyzed by 16S rDNA high-throughput sequencing. The study found that male BALB/c mice can successfully establish a typical model of small intestinal inflammation by freely drinking a 3% DSS solution for one week. L. rhamnosus 1.0320 combined with inulin can alleviate DSS-induced colitis, reduce the Disease Activity Index (DAI) score of the pathological damage of colon tissue, decrease myeloperoxidase (MPO) activity, increase hemoglobin content, and regulate the expression levels of inflammatory cytokines IL-1β, IL-6, TNF-α and IL-10. The intestinal flora of mice is reduced after enteritis, and its structure gets disordered. The combination of L. rhamnosus 1.0320 and inulin can increase the abundance and diversity of intestinal flora, and increase the content of beneficial bacteria. Prebiotics promote the colonization ability of probiotics. L. rhamnosus 1.0320 combined with inulin can change the intestinal flora to relieve ulcerative colitis, providing a new theoretical basis for the study of UC mechanism.